A sodium ferric pyrophosphate phosphate composite positive electrode material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611509284.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]有鉴于此,本发明提供了一种磷酸焦磷酸铁钠复合正极材料及其制备方法和应用,本发明提供的磷酸焦磷酸铁钠复合正极材料,通过钠位协同掺杂,有效解决了磷酸焦磷酸铁钠正极材料存在的钠离子扩散数量少、钠离子扩散动力学缓慢和比容量低等问题,协同提升了磷酸焦磷酸铁钠复合正极材料的比容量、倍率性能和循环寿命
本发明在总掺杂量受控的条件下,通过控制大离子半径的掺杂离子(例如K+:1.51Å、Rb+:1.61 Å)和小离子半径的掺杂离子(例如Li+:0.59 Å、Ca2+:1.0 Å)的种类与掺杂比例,调节Na亚晶格中的局部应变分布。晶体结构测试表明,K+单掺杂主要引起c轴和晶胞体积的正向变化,Li+单掺杂主要引起a轴和晶胞体积的负向变化;K+和Li+共同掺杂后的晶格响应并不符合上述单掺杂结果的线性叠加规律。特别是在K+和Li+为特定比例时,磷酸焦磷酸铁钠复合正极材料在保留适度c轴调节的同时,可显著减小晶胞体积偏移,形成各向异性晶格应变补偿状态。上述结构状态有利于兼顾钠离子迁移动力学和长循环过程中的结构稳定性,从而获得优于总掺杂量相同的K+单掺杂材料或Li+单掺杂材料的综合电化学性能。
Smart Images

Figure CN123017953A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a sodium iron pyrophosphate composite cathode material, its preparation method, and its application. Background Technology
[0002] Addressing the urgent need for large-scale electrochemical energy storage and low-temperature chemical power sources, sodium-ion batteries, with their core advantages such as abundant sodium resources, low cost, and excellent safety performance, are considered a promising new electrochemical energy storage technology. Sodium iron pyrophosphate cathode material, due to its suitable operating voltage (~3.1 V, vs Na...),... + With its high theoretical specific capacity (129 mAh / g) and low volume expansion rate (~4%), sodium-ion battery cathode material is considered a highly promising candidate. However, its application in sodium-ion batteries still faces key technical challenges, including low phase purity, low electronic conductivity, slow ion diffusion kinetics, poor long-cycle stability, and poor rate performance, which limit its practical electrochemical performance and large-scale application.
[0003] To address the aforementioned issues, current modification methods for sodium iron pyrophosphate cathode materials mainly include constructing Fe vacancies to suppress impurity phase formation, Fe-site doping to regulate electronic structure, Na-site doping to alter the local coordination environment of sodium ions, and surface carbon coating to enhance electronic conductivity. Among these, Na-site doping directly affects the reversible utilization of different Na sites, the sodium ion migration pathway, and the crystal structure evolution during charge and discharge. However, different dopants exert varying directions and amplitudes of control over crystal axis parameters and unit cell volume. Using a single dopant ion makes it difficult to simultaneously coordinate sodium ion migration channels, the utilization rate of active Na sites, and lattice strain. Therefore, establishing the intrinsic relationship between Na-site doping composition, anisotropic lattice response, and electrochemical performance remains a key technical problem that urgently needs to be solved for sodium iron pyrophosphate cathode materials.
[0004] Existing academic studies have reported small-radius Li + and large radius K + Single doping modulation of the Na-site in sodium iron pyrophosphate. Among them, Li... + Doping can restrict the displacement of Fe atoms and the distortion of P2O7 structural units under high voltage, maintaining the sodium ion migration pathway (ACS Sustainable Chem. Eng. 2025, 13, 4908~4915); K +Doping can create pillaring effects at specific Na sites, slowing down crystal structure evolution during sodium insertion / extraction and improving the kinetics of sodium ion insertion / extraction reactions (J. Energy Chem. 2025, 109, 931~940). The above studies show that ions of different radii can affect the local structure and electrochemical behavior of the Na sublattice, but the differences and advantages / disadvantages of large and small radius ions in regulating lattice structure and electrochemical performance at sodium sites are not clearly defined. In particular, after large / small radius ions co-enter the Na sublattice, whether the strain and cell volume changes along each crystal axis follow a linear superposition law of single doping results, and the correspondence between the doping ratio of large / small radius ions and the low lattice strain structural state, are not given.
[0005] Among the published patents, Chinese patent CN117727924A discloses the effect of sodium-iron dual-site doping on electrochemical performance, but the sodium site regulation part does not involve the synergistic doping research of large-radius and small-radius ions. Chinese patent CN117558905A focuses on the synergistic effect of sodium-iron dual-site doping and graphene coating, although K+ is simultaneously implemented at the sodium site... + / Li + Single-doping and synergistic-doping experiments were conducted, but due to the simultaneous introduction of two types of interfering variables—graphene coating and iron site doping—the study did not specifically investigate the large-radius K at the sodium site. + With small radius Li + The regulatory effect of synergistic doping on key structural features of cathode materials includes the Na-O coordination environment, cell volume variation, and crystal structure stability. The aforementioned structural regulation mechanism based on sodium site doping forms the core foundation for developing high-capacity, high-rate, and long-life cathode materials. Summary of the Invention
[0006] In view of this, the present invention provides a sodium iron pyrophosphate composite cathode material, its preparation method and application. The sodium iron pyrophosphate composite cathode material provided by the present invention effectively solves the problems of low sodium ion diffusion quantity, slow sodium ion diffusion kinetics and low specific capacity of sodium iron pyrophosphate cathode material through sodium site synergistic doping, and synergistically improves the specific capacity, rate performance and cycle life of sodium iron pyrophosphate composite cathode material.
[0007] This invention provides a sodium iron pyrophosphate composite cathode material, comprising sodium-doped sodium iron pyrophosphate cathode material and carbon, wherein the mass ratio of the sodium-doped sodium iron pyrophosphate cathode material to carbon is 1:0.01~0.1; the chemical formula of the sodium-doped sodium iron pyrophosphate cathode material is Na. 4-ax-by M x N yFe3(PO4)2P2O7, where M is a dopant ion with a large ionic radius, N is a dopant ion with a small ionic radius, a is the valence of M, b is the valence of N, 0 < x ≤ 0.3, 0 < y ≤ 0.3; a dopant ion with a large ionic radius refers to an ion with an ionic radius greater than that of a sodium ion, and a dopant ion with a small ionic radius refers to an ion with an ionic radius less than that of a sodium ion.
[0008] Preferably, doped ions with large ionic radii include K + and Rb + One or two of them.
[0009] Preferably, the doped ions with small ionic radii include Li + and Ca 2+ One or two of them.
[0010] This invention also provides a method for preparing the sodium iron pyrophosphate composite cathode material according to the above scheme, comprising the following steps: (1) According to the stoichiometric ratio in the chemical formula of sodium iron pyrophosphate cathode material with sodium site co-doping, the phosphorus source, iron source, sodium source, M source, N source, carbon source, dispersant and water are mixed and spray-dried to obtain precursor powder. (2) The precursor powder was heat-treated to obtain sodium iron pyrophosphate composite cathode material.
[0011] Preferably, the phosphorus source, iron source, sodium source, M source and N source are independent of each other (one raw material provides only one target element) or are the same (one raw material provides multiple target elements), with the provision of the target elements phosphorus, iron, sodium, M and N as the standard.
[0012] Preferably, the carbon source includes one or more of glucose, sucrose, ascorbic acid, cyclodextrin, citric acid, urea, and starch.
[0013] Preferably, the dispersant includes one or more of sodium polyacrylate, sodium carboxymethyl cellulose, polyethylene glycol, and polyvinylpyrrolidone.
[0014] Preferably, the inlet air temperature of the spray dryer is 120~200 ℃ and the outlet air temperature is 100~140 ℃.
[0015] Preferably, the heat treatment is carried out in a protective atmosphere; the heat treatment includes sequential pre-firing and calcination; the pre-firing includes sequential heating pre-firing and holding pre-firing; the heating rate of the heating pre-firing is 1~5 ℃ / min; the holding pre-firing temperature is 300~400 ℃ and the time is 3~8 h; the calcination includes sequential heating calcination and holding calcination; the heating rate of the heating calcination is 1~5 ℃ / min; the holding calcination temperature is 500~600 ℃ and the time is 5~12 h.
[0016] This invention also provides the application of the sodium iron pyrophosphate composite cathode material described above in the field of sodium-ion batteries.
[0017] Compared with the prior art, the present invention has achieved the following beneficial effects: This invention, under the condition of controlled total doping amount, controls the doping ions with large ionic radii (e.g., K+). + 1.51Å, Rb + 1.61 Å) and doped ions with small ionic radii (e.g., Li) + 0.59 Å, Ca 2+ The type and doping ratio of K (1.0 Å) were used to adjust the local strain distribution in the Na sublattice. Crystal structure tests showed that K + Single doping primarily causes positive changes in the c-axis and cell volume, Li + Single doping primarily causes negative changes in the a-axis and cell volume; K + and Li + The lattice response after co-doping does not conform to the linear superposition law of the single-doping results described above. Especially in K... + and Li + At a specific ratio, the sodium iron pyrophosphate composite cathode material can significantly reduce cell volume shift while retaining moderate c-axis adjustment, forming an anisotropic lattice strain-compensated state. This structural state is beneficial for balancing sodium ion migration kinetics and structural stability during long-cycle operation, thus achieving superior results compared to K with the same total doping amount. + Single-doped materials or Li + The overall electrochemical performance of single-doped materials.
[0018] This invention broadens the sodium ion migration path by introducing dopant ions with large ionic radii at the Na site, while simultaneously introducing dopant ions with small ionic radii to enhance the stability of the Na-O bond and effectively suppress lattice distortion during charge and discharge. This synergistically improves the specific capacity (initial discharge specific capacity), rate performance, and cycle life (cycle stability) of the sodium iron pyrophosphate composite cathode material, solving the key problems of low capacity and short life in practical applications of sodium iron pyrophosphate cathode materials.
[0019] This invention utilizes both large-radius and small-radius dopants to simultaneously replace a portion of sodium ions (1.02 Å). The large-radius dopants, with their larger ionic radii than sodium ions, expand the local unit cell structure of the sodium iron pyrophosphate crystal, broadening the migration channels for sodium ions and contributing to increased sodium ion migration and diffusion kinetics. The small-radius dopants, with their smaller radii and shorter Li / Ca-O bonds compared to Na-O bonds, exhibit a site pinning effect in the crystal structure, stabilizing the coordination environment around Na sites and effectively suppressing lattice distortion and unit cell volume changes during charge-discharge sodium insertion / extraction. The synergistic effect of the large-radius and small-radius dopants solves the bottleneck problem of simultaneously achieving optimal sodium ion migration, diffusion kinetics, and structural stability.
[0020] This invention, based on the synergistic design and regulation of sodium sites, not only alters the electrochemical activity of sodium ions at the Na site but also optimizes the Na-O coordination environment, thereby increasing the number of sodium ions extracted and the diffusion kinetics. More importantly, dopants with large and small ionic radii work synergistically; the former broadens the sodium ion diffusion channels while the latter stabilizes the Na-O bond, ensuring structural stability during the sodium insertion / extraction process, thus achieving both high capacity and long cycle life. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of this invention, the accompanying drawings used in the embodiments of this invention or in the prior art are briefly described below. For those skilled in the art, other drawings can be derived from the following drawings without creative effort, and all such drawings are within the protection scope of this invention.
[0022] Figure 1 The graph shows a comparison of the rate of change of unit cell parameters (a, c, and unit cell volume V) of the sodium iron pyrophosphate composite cathode materials prepared in Examples 2-3 and Comparative Examples 2-4 after Rietveld Refinement. Figure 2 The images are scanning electron microscope (SEM) images of the sodium iron pyrophosphate composite cathode materials prepared in Example 2 and Comparative Example 1; where a is the SEM image of the sodium iron pyrophosphate composite cathode material prepared in Example 2, and b is the SEM image of the sodium iron pyrophosphate composite cathode material prepared in Comparative Example 1. Figure 3 Rate performance curves of CR2032 coin cells prepared in Examples 2, 5, Comparative Example 1 and Comparative Example 3; Figure 4 The graphs show the cycling performance of CR2032 coin cells prepared in Examples 2, 5 and Comparative Examples 1-3 at a 5C rate. Detailed Implementation
[0023] This invention provides a sodium iron pyrophosphate composite cathode material, comprising sodium-doped sodium iron pyrophosphate cathode material and carbon, wherein the mass ratio of the sodium-doped sodium iron pyrophosphate cathode material to carbon is 1:0.01~0.1; the chemical formula of the sodium-doped sodium iron pyrophosphate cathode material is Na. 4-ax-by M x N y Fe3(PO4)2P2O7, where M is a dopant ion with a large ionic radius, N is a dopant ion with a small ionic radius, a is the valence of M, b is the valence of N, 0 < x ≤ 0.3, 0 < y ≤ 0.3.
[0024] In this invention, the mass ratio of sodium iron pyrophosphate cathode material co-doped with sodium sites to carbon is 1:0.01~0.1, specifically 1:0.05 or 1:0.08.
[0025] In this invention, a doped ion with a large ionic radius refers to an ion with an ionic radius greater than that of a sodium ion (1.02 Å), and a doped ion with a small ionic radius refers to an ion with an ionic radius less than that of a sodium ion (1.02 Å).
[0026] In this invention, doped ions with large ionic radii may include K + and Rb + One or two of them.
[0027] In this invention, the doped ions with small ionic radii may include Li. + and Ca 2+ One or two of them.
[0028] This invention also provides a method for preparing the sodium iron pyrophosphate composite cathode material according to the above scheme, comprising the following steps: (1) The phosphorus source, iron source, sodium source, M source, N source, carbon source, dispersant and water are mixed and spray-dried to obtain precursor powder; (2) The precursor powder was heat-treated to obtain sodium iron pyrophosphate composite cathode material.
[0029] The present invention involves mixing phosphorus source, iron source, sodium source, M source, N source, carbon source, dispersant and water (denoted as the first mixture) and spray drying to obtain precursor powder.
[0030] In this invention, the amounts of phosphorus source, iron source, sodium source, M source, and N source are determined to achieve the molar ratios in the chemical formula of the sodium iron pyrophosphate cathode material with sodium site co-doping.
[0031] In this invention, the phosphorus source, iron source, sodium source, M source and N source can be independent of each other (one raw material provides only one target element) or the same (one raw material provides multiple target elements), with the provision of the target elements phosphorus, iron, sodium, M and N as the standard.
[0032] In this invention, the phosphorus source can be a phosphate; the phosphate may include one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, and phosphoric acid.
[0033] In this invention, the iron source can be an iron salt; the iron salt can include one or more of ferric nitrate, ferric phosphate, ferrous oxalate, ferrous acetate, ferrous sulfate, ferric chloride, ferrous chloride, and ferric oxide.
[0034] In this invention, the sodium source can be a sodium salt; the sodium salt may include one or more of disodium hydrogen phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, sodium acetate, sodium oxalate, sodium citrate and sodium sulfate.
[0035] In this invention, the M source can be an M salt; the M salt can include one or two of potassium salts and rubidium salts; the potassium salt can include one or more of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium carbonate, potassium sulfate, potassium nitrate and potassium chloride; the rubidium salt can include one or more of rubidium chloride, rubidium carbonate, rubidium nitrate, rubidium dihydrogen phosphate and rubidium acetate.
[0036] In this invention, the N source can be an N salt; the N salt can include one or both of lithium salt and calcium salt; the lithium salt can include one or more of lithium chloride, lithium dihydrogen phosphate, lithium carbonate, lithium nitrate and lithium hydrogen phosphate; the calcium salt can include one or more of calcium chloride, calcium carbonate, calcium nitrate, calcium dihydrogen phosphate, calcium acetate and calcium sulfate.
[0037] In this invention, the carbon source may include one or more of glucose, sucrose, ascorbic acid, cyclodextrin, citric acid, urea, and starch.
[0038] In this invention, the dispersant may include one or more of sodium polyacrylate, sodium carboxymethyl cellulose, polyethylene glycol, and polyvinylpyrrolidone.
[0039] The present invention does not limit the amount of dispersant used; conventional amounts in the art can be used.
[0040] In this invention, the water can be deionized water.
[0041] In this invention, the first mixing may include the following steps: stirring and mixing phosphate, iron salt, sodium salt, M salt, N salt, carbon source and water to obtain a mixed solution, and then mixing the mixed solution with a dispersant to obtain a mixed slurry.
[0042] In this invention, the solid content of the mixed slurry can be 20~50 wt%, specifically 25 wt%, 30 wt%, 35 wt%, 40 wt% or 45 wt%.
[0043] In this invention, the inlet air temperature of the spray dryer can be 120~200 ℃, specifically 150 ℃ or 180 ℃, and the outlet air temperature can be 100~140 ℃, specifically 110 ℃, 120 ℃ or 130 ℃.
[0044] After obtaining the precursor powder, the present invention performs heat treatment on the precursor powder to obtain sodium iron pyrophosphate composite cathode material. In this invention, heat treatment can be performed in a protective atmosphere; the protective atmosphere can be argon, nitrogen, or an argon-hydrogen mixture; the volume fraction of hydrogen in the argon-hydrogen mixture can be 5%~10%; the heat treatment can include sequential pre-firing and calcination; pre-firing can include sequential heating pre-firing and holding pre-firing; the heating rate of heating pre-firing can be 1~5 °C / min, specifically 3 °C / min; the holding pre-firing temperature can be 300~400 °C, specifically 350 °C, and the time can be 3~8 h, specifically 4 h, 5 h, 6 h, or 7 h; calcination can include sequential heating calcination and holding calcination; the heating rate of heating calcination can be 1~5 °C / min, specifically 3 °C / min; the holding calcination temperature can be 500~600 °C, specifically 530 °C, 550 °C, or 580 °C, and the time can be 5~12 h, specifically 7 h, 9 h, or 11 h.
[0045] This invention also provides the application of the sodium iron pyrophosphate composite cathode material described above in the field of sodium-ion batteries.
[0046] In this invention, the sodium-ion battery can be a secondary battery.
[0047] To further illustrate the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments.
[0048] Example 1: This embodiment provides a sodium iron pyrophosphate composite cathode material, including sodium iron pyrophosphate cathode material with sodium site co-doping (Na 3.8 Rb 0.1 Li 0.1 The mass ratio of Fe3(PO4)2P2O7) and carbon, sodium pyrophosphate co-doped cathode material to carbon is 1:0.02.
[0049] The preparation steps of the sodium iron pyrophosphate composite cathode material in this embodiment are as follows: S1. Weigh ferric nitrate, sodium pyrophosphate, lithium chloride, rubidium chloride, disodium hydrogen phosphate, citric acid, and sucrose according to the molar ratio in the chemical formula of sodium iron pyrophosphate cathode material with sodium site co-doping and the above mass ratio, and add them to deionized water. Stir well to obtain a mixed solution. S2. Sodium polyacrylate (2 wt% of ferric nitrate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the mixed slurry is 35 wt%, the inlet air temperature is 180 ℃, and the outlet air temperature is 110 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 350 °C at a heating rate of 4 °C / min under an argon-hydrogen mixed atmosphere (the volume fraction of hydrogen in the argon-hydrogen mixed gas is 10%), and held for 5 h; then heated to 500 °C at a heating rate of 4 °C / min and held for 12 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0050] Example 2: This embodiment provides a sodium iron pyrophosphate composite cathode material, including sodium iron pyrophosphate cathode material with sodium site co-doping (Na 3.97 K 0.02 Li 0.01 The mass ratio of sodium iron pyrophosphate cathode material (Fe3(PO4)2P2O7) and carbon, with sodium sites co-doped, is 1:0.03.
[0051] The preparation steps of the sodium iron pyrophosphate composite cathode material in this embodiment are as follows: S1. Weigh iron phosphate, sodium dihydrogen phosphate, sodium carbonate, potassium dihydrogen phosphate, lithium dihydrogen phosphate, citric acid and glucose according to the molar ratio in the chemical formula of sodium iron pyrophosphate sodium cathode material with sodium site co-doping and the above mass ratio, and add them to deionized water. Stir evenly to obtain a mixed solution. S2. Polyethylene glycol (3 wt% of ferric phosphate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 30 wt%, the inlet air temperature is 160 ℃, and the outlet air temperature is 100 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 300 ℃ at a heating rate of 3 ℃ / min under an argon atmosphere, and held for 3 h; then heated to 550 ℃ at a heating rate of 3 ℃ / min and held for 10 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0052] Example 3: This embodiment provides a sodium iron pyrophosphate composite cathode material, including sodium iron pyrophosphate cathode material with sodium site co-doping (Na3.97 K 0.01 Li 0.02 The mass ratio of Fe3(PO4)2P2O7) and carbon, sodium pyrophosphate co-doped cathode material to carbon is 1:0.02.
[0053] The preparation steps of the sodium iron pyrophosphate composite cathode material in this embodiment are as follows: S1. Weigh iron phosphate, sodium dihydrogen phosphate, sodium carbonate, potassium dihydrogen phosphate, lithium dihydrogen phosphate, citric acid and glucose according to the molar ratio in the chemical formula of sodium iron pyrophosphate sodium cathode material with sodium site co-doping and the above mass ratio, and add them to deionized water. Stir evenly to obtain a mixed solution. S2. Polyethylene glycol (3 wt% of ferric phosphate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 30 wt%, the inlet air temperature is 160 ℃, and the outlet air temperature is 100 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 300 ℃ at a heating rate of 3 ℃ / min under an argon atmosphere, and held for 3 h; then heated to 550 ℃ at a heating rate of 3 ℃ / min and held for 10 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0054] Example 4: This embodiment provides a sodium iron pyrophosphate composite cathode material, including sodium iron pyrophosphate cathode material with sodium site co-doping (Na 3.955 K 0.015 Ca 0.015 The mass ratio of Fe3(PO4)2P2O7) and carbon, sodium pyrophosphate co-doped cathode material to carbon is 1:0.02.
[0055] The preparation steps of the sodium iron pyrophosphate composite cathode material in this embodiment are as follows: S1. Weigh iron oxide, ammonium dihydrogen phosphate, sodium carbonate, potassium nitrate, calcium acetate, ascorbic acid, and starch according to the molar ratio in the chemical formula of sodium iron pyrophosphate sodium cathode material with sodium site co-doping and the above mass ratio, and add them to deionized water. Stir evenly to obtain a mixed solution. S2. Sodium carboxymethyl cellulose (2 wt% of iron oxide) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 40 wt%, the inlet air temperature is 200 ℃, and the outlet air temperature is 140 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 350 ℃ at a heating rate of 5 ℃ / min under a nitrogen atmosphere, and held for 3 h; then heated to 600 ℃ at a heating rate of 5 ℃ / min and held for 8 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0056] Example 5: This embodiment provides a sodium iron pyrophosphate composite cathode material, including sodium iron pyrophosphate cathode material with sodium site co-doping (Na 3.97 K 0.015 Li 0.015 The mass ratio of Fe3(PO4)2P2O7) and carbon, sodium pyrophosphate co-doped cathode material to carbon is 1:0.02.
[0057] The preparation steps of the sodium iron pyrophosphate composite cathode material in this embodiment are as follows: S1. Weigh iron phosphate, sodium dihydrogen phosphate, sodium carbonate, potassium dihydrogen phosphate, lithium dihydrogen phosphate, citric acid and glucose according to the molar ratio in the chemical formula of sodium iron pyrophosphate sodium cathode material with sodium site co-doping and the above mass ratio, and add them to deionized water. Stir evenly to obtain a mixed solution. S2. Polyethylene glycol (3 wt% of ferric phosphate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 30 wt%, the inlet air temperature is 160 ℃, and the outlet air temperature is 100 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 300 ℃ at a heating rate of 3 ℃ / min under an argon atmosphere, and held for 3 h; then heated to 550 ℃ at a heating rate of 3 ℃ / min and held for 10 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0058] Comparative Example 1: This comparative example provides a sodium iron pyrophosphate composite cathode material, comprising Na4Fe3(PO4)2P2O7 cathode material and carbon, wherein the mass ratio of Na4Fe3(PO4)2P2O7 cathode material to carbon is 1:0.03.
[0059] The preparation steps of the sodium iron pyrophosphate composite cathode material in this comparative example are as follows: S1. Sodium dihydrogen phosphate, sodium carbonate, iron phosphate, citric acid and glucose are weighed according to the molar ratio in the chemical formula of Na4Fe3(PO4)2P2O7 cathode material and the above mass ratio, and then added to deionized water and stirred evenly to obtain a mixed solution. S2. Polyethylene glycol (3 wt% of ferric phosphate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 30 wt%, the inlet air temperature is 160 ℃, and the outlet air temperature is 100 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 300 ℃ at a heating rate of 3 ℃ / min under an argon atmosphere, and held for 3 h; then heated to 550 ℃ at a heating rate of 3 ℃ / min and held for 10 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0060] Comparative Example 2: This comparative example provides a sodium iron pyrophosphate composite cathode material, including Na 3.97 K 0.03 Fe3(PO4)2P2O7 cathode material and carbon, Na 3.97 K 0.03 The mass ratio of Fe3(PO4)2P2O7 cathode material to carbon is 1:0.03.
[0061] The preparation steps of the sodium iron pyrophosphate composite cathode material in this comparative example are as follows: S1. Sodium dihydrogen phosphate, sodium carbonate, ferric phosphate, potassium dihydrogen phosphate, citric acid, and glucose are respectively prepared according to Na... 3.97 K 0.03 After weighing the molar ratio in the chemical formula of Fe3(PO4)2P2O7 cathode material and the above mass ratio, add it to deionized water and stir evenly to obtain a mixed solution. S2. Polyethylene glycol (3 wt% of ferric phosphate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 30 wt%, the inlet air temperature is 160 ℃, and the outlet air temperature is 100 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 300 ℃ at a heating rate of 3 ℃ / min under an argon atmosphere, and held for 3 h; then heated to 550 ℃ at a heating rate of 3 ℃ / min and held for 10 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0062] Comparative Example 3: This comparative example provides a sodium iron pyrophosphate composite cathode material, including Na 3.97 Li 0.03 Fe3(PO4)2P2O7 cathode material and carbon, Na 3.97 Li 0.03 The mass ratio of Fe3(PO4)2P2O7 cathode material to carbon is 1:0.03.
[0063] The preparation steps of the sodium iron pyrophosphate composite cathode material in this comparative example are as follows: S1. Sodium dihydrogen phosphate, sodium carbonate, ferric phosphate, lithium dihydrogen phosphate, citric acid, and glucose are respectively prepared according to Na... 3.97 Li 0.03 After weighing the molar ratio in the chemical formula of Fe3(PO4)2P2O7 cathode material and the above mass ratio, add it to deionized water and stir evenly to obtain a mixed solution. S2. Polyethylene glycol (3 wt% of ferric phosphate) is added to the mixed solution to obtain a mixed slurry, which is then spray-dried. The solid content of the slurry is 30 wt%, the inlet air temperature is 160 ℃, and the outlet air temperature is 100 ℃ to obtain the precursor powder. S3. The precursor powder is transferred to a tube furnace and heated to 300 ℃ at a heating rate of 3 ℃ / min under an argon atmosphere, and held for 3 h; then heated to 550 ℃ at a heating rate of 3 ℃ / min and held for 10 h to complete the calcination and obtain sodium iron pyrophosphate composite cathode material.
[0064] Test Example 1: The sodium iron pyrophosphate composite cathode materials prepared in Examples 2, 3, 5, Comparative Example 2, and Comparative Example 3 were subjected to X-ray diffraction (XRD) tests and Rietveld refinement. The rate of change of the refined cell parameters (a, c, and cell volume V) is as follows: Figure 1 As shown.
[0065] according to Figure 1 It can be seen that K in Comparative Example 2 + The doped sodium iron pyrophosphate composite cathode material mainly causes positive changes in the c-axis and cell volume, as seen in Comparative Example 3 with Li. + The doped sodium iron pyrophosphate composite cathode material mainly causes negative changes in the a-axis and cell volume; the lattice response of the sodium iron pyrophosphate composite cathode materials prepared by sodium site co-doping in Examples 2, 3, and 5 does not conform to the linear superposition law of the above single doping results. Especially in Example 2, K + and Li + At a molar ratio of 2:1, the sodium iron pyrophosphate composite cathode material can significantly reduce cell volume shift while retaining moderate c-axis adjustment, forming an anisotropic lattice strain-compensated state. This structural state is beneficial for balancing sodium ion migration kinetics and structural stability during long-term cycling.
[0066] Test Example 2: The sodium iron pyrophosphate composite cathode materials prepared in Example 2 and Comparative Example 1 were observed using a scanning electron microscope, and the results are as follows: Figure 2 As shown.
[0067] according to Figure 2 As can be seen, the sodium iron pyrophosphate composite cathode material prepared in Example 2 consists of micron-sized particles with higher sphericity, more regular contours, uniform surface pore distribution and pore size, and more dense particle packing. In contrast, the sodium iron pyrophosphate composite cathode material prepared in Comparative Example 1 consists of micron-sized particles with slightly lower sphericity and relatively uneven pore size, exhibiting large pores and loose gaps. The sodium iron pyrophosphate composite cathode material prepared in Example 2 possesses a dense and relatively uniform porous structure, which not only facilitates sodium ion diffusion but also ensures structural stability during sodium insertion / extraction, thereby achieving high rate capability and long cycle life performance.
[0068] Test Example 3: The sodium iron pyrophosphate composite cathode materials prepared in Examples 2, 5, 1, 2, and 3 were used as active materials and dispersed in N-methylpyrrolidone (NMP, NMP:PVDF=20:1) solvent with super-P and PVDF (polyvinylidene fluoride) at a mass ratio of 70:20:10. The mixtures were then ground uniformly to obtain cathode slurry. The positive electrode slurry was uniformly coated onto aluminum foil (coating thickness 25 μm), vacuum dried at 80 ℃ for 12 h (vacuum degree -0.1 MPa), and cut into 12 mm diameter discs to serve as the positive electrode of the sodium-ion battery. A metallic sodium sheet was used as the negative electrode, glass fiber as the separator, and 1.0 mol / L sodium perchlorate as the electrolyte (where the volume ratio of PC to FEC was PC:FEC = 95:5). CR2032 coin cells were assembled in a glove box. The rate performance of the CR2032 coin cells assembled in Examples 2 and 5, and Comparative Examples 1 and 3 was tested, and the results are as follows: Figure 3 As shown.
[0069] according to Figure 3 It can be seen that the discharge specific capacity of Example 2 at all rates is higher than that of Comparative Example 1 and Comparative Example 3, with discharge specific capacities of 104.4 mAh g⁻¹ at 0.2 C, 0.5 C, 1 C, 2 C, 5 C, and 10 C, respectively. -1 100.4 mAh g -1 98.6 mAh g -1 96.7 mAh g -1 92.7 mAh g -1 and 87.6 mAh g -1 It exhibits superior rate performance. Example 5 shows significantly higher discharge specific capacity at 1 C, 2 C and 5 C than Comparative Example 1 and Comparative Example 3, indicating that its rate performance is superior.
[0070] Further testing was conducted on the cycle performance of the CR2032 coin cells assembled in Examples 2, 5, Comparative Examples 1, 2, and 3 at 5 C. The results are as follows: Figure 4 As shown.
[0071] according to Figure 4 It can be seen that the CR2032 coin cell assembled in Example 2 still has a discharge specific capacity of 79.9 mAh g after 1000 cycles at 5 C. -1 The CR2032 coin cell assembled in Example 5 performs similarly to Example 2 after up to 400 cycles at 5C, and has a discharge specific capacity of 74.7 mAh g after 1000 cycles. -1 Slightly lower than Example 2, but still significantly higher than Comparative Example 1 (24.9 mAh g). -1 Comparative Example 2 (63.2 mAh g) -1 ) and Comparative Example 3 (63.1 mAh g) -1 The CR2032 coin cell assembled in Example 2 retained 87.1% of its capacity after 1000 cycles at 5 C, and the CR2032 coin cell assembled in Example 5 retained 82% of its capacity after 1000 cycles at 5 C, both demonstrating good cycle life.
[0072] The embodiments of the present invention have been described above; however, these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. All other embodiments obtained by those skilled in the art based on the above embodiments of the present invention without inventive effort are within the protection scope of the present invention.
Claims
1. A sodium iron pyrophosphate composite cathode material, characterized in that, The cathode material includes sodium iron pyrophosphate co-doped with sodium sites and carbon, with a mass ratio of sodium iron pyrophosphate co-doped with sodium sites to carbon of 1:0.01~0.
1. The chemical formula of the sodium iron pyrophosphate cathode material with sodium site co-doping is Na 4-ax-by M x N y Fe3(PO4)2P2O7, where M is a dopant ion with a large ionic radius, N is a dopant ion with a small ionic radius, a is the valence of M, b is the valence of N, 0 < x ≤ 0.3, 0 < y ≤ 0.3; Large ionic radius doped ions are those with an ionic radius greater than that of sodium ions, while small ionic radius doped ions are those with an ionic radius smaller than that of sodium ions.
2. The sodium iron pyrophosphate composite cathode material according to claim 1, characterized in that, Large ionic radius doped ions include K + and Rb + One or two of them.
3. The sodium iron pyrophosphate composite cathode material according to claim 1, characterized in that, Small ionic radius doped ions include Li + and Ca 2+ One or two of them.
4. A method for preparing a sodium iron pyrophosphate composite cathode material, characterized in that, The sodium iron pyrophosphate composite cathode material is the sodium iron pyrophosphate composite cathode material according to any one of claims 1 to 3, comprising the following steps: (1) According to the stoichiometric ratio in the chemical formula of sodium iron pyrophosphate cathode material with sodium site co-doping, the phosphorus source, iron source, sodium source, M source, N source, carbon source, dispersant and water are mixed and spray-dried to obtain precursor powder. (2) The precursor powder was heat-treated to obtain sodium iron pyrophosphate composite cathode material.
5. The method for preparing the sodium iron pyrophosphate composite cathode material according to claim 4, characterized in that, The phosphorus source, iron source, sodium source, M source and N source are independent of each other or are the same, with the aim of providing the target elements phosphorus, iron, sodium, M and N.
6. The method for preparing the sodium iron pyrophosphate composite cathode material according to claim 4, characterized in that, Carbon sources include one or more of glucose, sucrose, ascorbic acid, cyclodextrin, citric acid, urea, and starch.
7. The method for preparing the sodium iron pyrophosphate composite cathode material according to claim 4, characterized in that, The dispersant includes one or more of sodium polyacrylate, sodium carboxymethyl cellulose, polyethylene glycol, and polyvinylpyrrolidone.
8. The method for preparing the sodium iron pyrophosphate composite cathode material according to claim 4, characterized in that, The inlet air temperature for spray drying is 120~200 ℃, and the outlet air temperature is 100~140 ℃.
9. The method for preparing the sodium iron pyrophosphate composite cathode material according to claim 4, characterized in that, Heat treatment is carried out in a protective atmosphere; The heat treatment includes pre-firing and calcination in sequence; Pre-firing includes sequential heating pre-firing and heat preservation pre-firing; The heating rate for preheating is 1~5 ℃ / min; The temperature for heat preservation and preheating is 300~400 ℃, and the time is 3~8 h; Calcination includes sequentially heating and calcining, followed by heat preservation and calcination. The heating rate for calcination is 1~5 ℃ / min; The calcination temperature is 500~600 ℃, and the time is 5~12 h.
10. The application of a sodium iron pyrophosphate composite cathode material in the field of sodium-ion batteries, characterized in that, The sodium iron pyrophosphate composite cathode material is the sodium iron pyrophosphate composite cathode material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Sodium-iron double-doped polyanion positive electrode material and preparation method thereof
CN117558905A
Double-site doped iron-based phosphate composite material as well as preparation method and application thereof
CN117727924A